Evaluating the effect of bleomycin sulfate on oral keratotic lesions - E. Yazdi; F. Agha hoseini (Tehran University of Medical Sciences, 1997)
Non-removable Keratotic lesions are relatively prevalent in various types in oral mucosa. The treatment modality is often problematic and is done by using  various specific regimens. Bleomycin was used in two primary studies with limited number of patients (N=9) . In current survey, more patients were recruited in a longer period of study. In fact, 50 leukoplakia and lichen planus patients were treated by local administration of belomycin  in a 21 months follow-up period. Statistical analysis was done by using Kaplan meier and cox Regression methods. The obtained results showed that belomycin can remove many of these lesions and can prevent both chronic pattern and malignant changes of the lesions. As In 9 cases of leukoplakia, 2 cases of recurrence were recorded. According to statistical analysis, in case of complete treatment up to 11 months , the recurrence  would not be possible. In 41 cases of lichen planus, recurrence rate was higher and after  a longer period (17 months ) following complete treatment, recurrence was totally eliminated. In fact, Recurrence can be due to psychological conditions. To conclude, local administration of Bleomycin is recommended to use to treat Oral  keratotic lesions and can act successfully based on current study's findings.